Apakah Country Of Origin, Celebrity Endorsement, dan eWOM yang Dimediasi oleh Citra Merek dapat Memprediksi Niat Membeli Produk Skincare? - Christian Halim; Keni Keni (Universitas Bunda Mulia, 2022)
The increasing awareness of the Indonesian people to preserve their facial skin has invite many brands of skincare products to compete in the Indonesian market make the competition among them are increasingly fierce. So to excel in the competition, it is necessary to build a consumer's purchase intention. There are various factors that can lead to consumer purchase intentions, including country of origin, celebrity endorsement, and electronic word of mouth (eWOM) which can also form a brand image. The purpose of this study is to investigate the role of country of origin, celebrity endorsement, and electronic word of mouth (eWOM) on purchase intention either directly or through brand image. The study used a quantitative research design. Data collection used a cross sectional approach. A total of 192 respondents filled out a online questionnaire through the google form that was sent to the respondents. The data were analyzed using a structural equation model using Smart-PLS. The results showed that country of origin, celebrity endorsement, and electronic word of mouth (eWOM) can positively predict purchase intention, but country of origin cannot predict positively brand image, while celebrity endorsement and electronic word of mouth (eWOM) can positively predict brand image. In addition, brand image can also positively predict purchase intention. Country of origin and electronic word of mouth (eWOM) cannot positively predict purchase intention through brand image, while celebrity endorsements can positively predict purchase intention through brand image.